The rational organization of analytical accounting in the military units - O.A. Pinchuk (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
works which have been devoted to the issue of analytical accounting of fixed assets in military units. In the conditions of a hybrid war in Ukraine, an effective accounting system in military units is required, due to the specifics of their organizational, economic and technological features, which would allow responding quickly to modern challenges. The article considers one of the most important areas of accounting for military units, namely, accounting for fixed assets, its analytical support. An effectively structured analytics structure should ensure the effective and timely execution of tasks assigned to military units in accordance with current legislation. Suggestions for building a rational model of organization of analytical accounting of fixed assets in military units are given. The following levels of analytical accounting in military units are proposed: by purpose of property, by places of storage, by technical characteristics, by funds of military camps and by relevant services. The components of accounting for missile and artillery armament of tanks (self-propelled artillery units, infantry fighting vehicles, armored personnel carriers, and other military equipment) have been separately identified. The construction of the analytical system took into account the specifics of the sphere of activity of the business entity, which determines the individual nature of information flows in the system of management analysis of production and economic activities of the institution.